Determinants of tax avoidance: institutional ownership as a moderating variable - Pambudi Bowo Leksono; Kesi Widjajanti; Ardiani Ika Sulistyawati (Enrichment : Journal of Management, 2023)
This study aims to determine the effect of leverage, profitability, and transfer pricing on tax avoidance with institutional ownership as a moderating variable. The research population consists of manufacturing sector companies listed on the Indonesia Stock Exchange. Through purposive sampling, a sample of 35 companies was obtained from 2017 to 2021. The analysis technique used is panel data regression with Moderated Regression Analysis (MRA) through the Eviews 9 application. The test results using the Random Effect Model (REM) approach show that leverage has a negative effect on tax avoidance, profitability has a positive effect on tax avoidance, transfer pricing does not effect on tax avoidance, institutional ownership is not able to moderate the effect of leverage, profitability, and transfer pricing on tax avoidance.